2010
DOI: 10.1299/jmmp.4.1296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solution Treatment Temperature on Trigger Stress for Stress Induced Martensitic Transformation in Ti-10V-2Fe-3Al Alloy

Abstract: Effect of solution treatment temperature on trigger stress for stress induced martensitic transformation (SIMT) in Ti-10V-2Fe-3Al alloy has been investigated. The Ti-10V-2Fe-3Al tensile specimens were solution treated at 700-900℃ and quenched to room temperature in water. All specimens, except the one solution treated at 700℃, experienced the SIMT when subjected to tensile deformation. The trigger stress was observed to initially decrease with the solution temperature increasing from 720℃ to 760℃. However, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…[26] The b phase has a low Mo eq of approximately 7.6 wt pct in the b-ST Ti1023 alloy in the current work. [27] Therefore, SIMT became a dominant deformation mode as the external stress reached a trigger stress of SIMT. The first batch of a¢¢ martensite plates freely nucleated and grew through full grains of the original b parent phase because of their thermodynamically favorable conditions.…”
Section: A Deformation Mode Selectionmentioning
confidence: 99%
“…[26] The b phase has a low Mo eq of approximately 7.6 wt pct in the b-ST Ti1023 alloy in the current work. [27] Therefore, SIMT became a dominant deformation mode as the external stress reached a trigger stress of SIMT. The first batch of a¢¢ martensite plates freely nucleated and grew through full grains of the original b parent phase because of their thermodynamically favorable conditions.…”
Section: A Deformation Mode Selectionmentioning
confidence: 99%
“…However, it is essential to acknowledge that future refinements, to improve the computational efficiency, might be made to better align with the observed preferential transformation systems found in these alloys. In a manner akin to what is typically done for NiTi SMA's [23][24][25][26]. At the microscale the transformation systems can be described by the habit plane normal vector m (α) 0 and the shape strain vector b (α) 0 .…”
Section: Discussionmentioning
confidence: 99%
“…The conditions to induced SIM are usually quantified with the trigger stress. This is the point at which SIM is initiated in metastable β titanium alloys [11,12,17,21,23]. Trigger stress was found to rise linearly with logarithmic strain rate [16,25,26].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Material parameters for the two phases used in this study were found by calibrating the model against tensile test results of Ti-1023 alloy at room temperature and at a strain rate of 1 mm/min. As received alloy was heat treated at 700° C for 1 hour and then water quenched [22]. Volume fractions of the phases were found to be 40% and 60% phase [23].…”
Section: Parameter Identificationmentioning
confidence: 99%